Forskning i professionspraksis - Schwartz, Ida; Mardahl-Hansen, Tilde; Nielsen, Anna Sejer (Tidsskrift for Professionsstudier, 2020)
Taking its point of departure in an inclusion-research, social-practice-theory, and practice-research commitment, the article discusses how research at university colleges may be applicable relative to professionals’ work with inclusion. Thus, the article establishes a close link between the understanding of research into professions and the understanding of the practice of professions. The fundamental basis is a criticism of notions that research at university colleges is charged with the provision of solutions to well-defined problems in professional practice. An empirical example demonstrates the significance of research that contributes with knowledge about how professionals work actively with the transformation of dilemmas that are linked with problem understanding as well as participatory conditions under contradictory organisational conditions.